Bridging the Skills Gap between Work and Education
XVIII, 226 p.
Keywords: This book takes up the debate about matching vocational education with the labour market and shows progress in terms of theoretical models, tools (transformation and matching processes), and learning environments. The solutions, showing up the need for core or key skills, the necessity of embedding learning skills in authentic and guided learning environments, shows a perspective of research and developmen-tal work to be tested in schools and in workplaces, to find better curricula for a better skilling.